Odpowiedzi

2009-05-18T18:13:10+02:00
A) 3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
-5x+16=2x+10
-7x=-6
7x=6
x=6:7

b) 2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
x+6=-x-1
2x=-7
x=-3,5

c) 2(x-3)-4(3+x=-3(x+2)+2(2x-1)
2x-6-12+4x=4x-2
6x-18=4x-2
2x=16
x=8

d) 6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
3x+12=5x-6
-2x=-18
2x=18
x=9
2009-05-18T18:18:42+02:00
A)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-5x=-6/:(-5)
x=1 1/5
b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
4x+x=-1+6-12
5x=-7/:5
x=-1 2/5
c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
-3x=10/:(-3)
x=-3 1/3
d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-6-6
-2x=-18/(-2)
x=9
2009-05-18T18:26:38+02:00
A.3(x-4)-4(2x-7)=2(x+5)
3x-12-6x-+28=2x+10
3x+6x+2x=12+10
11x=22
x=2
b.2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
2x=-7
x=-3.5
c.2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
5x=10
x=2
d.6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+1+6-3x=4x-2-4+x
6x-3x-4x-x=1-6-2-4
-2x=-11
x=-9